Physical, functional, structural, and pasting characteristics of durian (Durio zibenthinus Murr.) seed flour from Kalimantan, Indonesia - Permatasari, Nelsy Dian; Witoyo, Jatmiko Eko; Masruri; Yuwono, Sudarminto Setyo; Widjanarko, Simon Bambang (Asia-Pacific Journal of Science and Technology, 2025)
Durian, native to Southeast Asia, particularly Indonesia, produces several by-products, including durian seed flour (DSF). Although DSF has gained research interest, its characteristics from Kalimantan, Indonesia remain underexplored compared to those from Thailand and Malaysia. This study investigates the physical, functional, structural, and pasting properties of DSF from West Kalimantan (DSF-WK), representing local durian varieties, and compares it with commercially available DSF in Indonesia (CDSF). Results demonstrated that the DSF-WK had higher lightness (L*), whiteness, swelling power, and water absorption capacity, but lower redness (a*), yellowness (b*), and oil absorption capacity than CDSF. Morphological analysis using SEM-EDX showed both flours had polygonal shapes, with DSF-WK containing carbon (C), oxygen (O), magnesium (Mg), phosphorus (P), and potassium (K), while CDSF contained only C, O, and K. FTIR analysis confirmed similar functional groups in both samples, including C-H, C-O-H, C-O, C-C, C-H₂, and O-H bonds. In addition, the type A-diffraction pattern reflects both the DSF samples. Pasting property analysis via Rapid Visco Analyzer (RVA) revealed DSF-WK had higher peak, trough, and final viscosities, indicating greater thickening ability, but lower breakdown, setback viscosities, peak time, and pasting temperature. Overall, DSF-WK is distinguished by its white color, superior water interaction properties, and distinctive pasting behavior. These features suggest its potential use in food products like noodles and cookies, which require brightness and viscosity. Moreover, its higher swelling power and water solubility suggest its suitability as a base for edible films, highlighting DSF-WK as a promising functional ingredient in food and packaging applications.